Victim and objective imputation - Teixidor Vinjoy, Duvi Alfredo (2011)
An approximation to the theory of victim blaming, from the objective accusation of a behavior, with emphasis on the interpretation of the finalism, systematic relocation of maliciousness, recklessness and the importance of the theory of the objective accusation in the expression of the meaning and sense of the typical identity. The approach ranges from the historical evolution of the conception of the accusation to the current condition of the discussion on the subject: a) establishment of the scope and the specific content of the norm, in other words the objective accusation; and b) the importance of the principle of self-responsibility of the victim  in the accusation, as a «recalcitrating normative experience», in an attempt to a) place emphasis on the standardization of the objective and subjective identity as an assumed reference of disvalue and b) rank the fundamental principle of proportionality upon attributing a behavior to its perpetrator, in situations of joint organization. Based on its dogmatic evolution, specific cases are analyzed, identifying the criteria used by the Courts to accuse the victim; a pragmatic vision of the criminal dogma that justifies the structuring of the violation of due care as a normative organizational institution, based on the reinterpretation of articles 18 and 59, paragraph 2 of the Criminal Code, with the purpose of a) preventing the separation of recklessness from the victim’s self-responsibility and b) facilitating a normative solution of a comprehensive tipicity to address the problems of the objective and subjective ascription of the behavior and its expression based on the disvalue of the act.